The application and trend of ultra-weak photon emission in biology and medicine - Du, Jinxin; Deng, Tingting; Cao, Baorui; Wang, Zhiying; Yang, Meina; Han, Jinxiang (Frontiers in Chemistry, 2023)
Ultra-weak bioluminescence, also known as ultra-weak photon emission(UPE), is one of the functional characteristics of biological organisms, characterized by specialized, low-energy level luminescence. Researchers have extensively studied UPE for decades, and the mechanisms by which UPE is generated and its properties have been extensively investigated. However， there has been a gradual shift in research focus on UPE in recent years toward exploring its application value. To better understand the application and trend of UPE in biology and medicine, we have conducted a review of relevant articles in recent years. Among the several topics covered in this review is UPE research in biology and medicine (including traditional Chinese medicine), primarily focused on UPE as a promising non-invasive tool for diagnosis and oxidative metabolism monitoring as well as a potential tool for traditional Chinese medicine research.